AB0385 A Randomized Controlled Clinical TRIAL to Evaluate the Efficacy of Recombinant Human Tumor Necrosis Factor-α Receptor II Fusion Protein in Juvenile Idiopathic Arthritis. (10th June 2014) - Zeng, H.; Zeng, P.; Xie, Y.; Tang, Y.; Li, F.
Abstract : Objectives: Research the Recombinant Human Tumor Necrosis Factor-α Receptor type II fusion protein antibody (Etanercept)for Treatment of juvenile idiopathic arthritis (JIA).A randomized controlled clinical trial was conducted, so as to provide evidence to better use of this drug in clinical application. Methods: Randomized principle was applied to divide the 124 JIA cases into control and treatment group. Slow-acting antirheumatic, nonsteroidal drugs or adrenocortical hormone were applied in these cases as basic drugs. There are no significant differences (P>0.05) of clinical classification and basic treatment between the two groups.62 cases of treatment group achieved subcutaneous Etanercept, 0.8mg/kg per week with a six mouths' period of treatment. The group included 17 oligoarticular cases (27.4 2%), 15 polyarticular cases (24.19%) and 30 SO-JIA cases (48.38%). The ACR Ped - 30, 50, 70 were used to assess the clinical efficacy. The occurrence of adverse reactions are monitored and recorded at the same time. Results: The remission rate of different cases in treatment group was different at each time point (P<0.05). The clinical remission rate of SO-JIA cases was lower compared with the two other types (P<0.05).The SO-JIA cases achieved 44% ACR Pedi50 remission after 3 months' treatment, and after 6 months' treatment they received 40.7% ACR Pedi50 remission and 29.6%ACR Pedi70 remission. The oligoarticular cases and polyarticular cases didn't have obvious difference in ACR Pedi30, 50, 70 remission rates at different time.80% of these cases had ACR Pedi50 remission after 6 months' treatment and above 50% had ACR Pedi70 remission. These were significantly different (P<0.05)compared with the control group. In the SO-JIA treatment group, Etanercept was effective in 3 SOJIA-MAS cases that conventional treatment didn't help and this did not conform to the report in the literature. 2 So - JIA cases merged with muscular stiffness after 1 week treatment.5 So-JIA cases had upper respiratory tract infection, diarrhea and other infection for several times during the treatment, one of them had chickenpox infection. They all got remission after drug withdrawal and symptomatic treatment. The adverse reactions of SO-JIA subgroups were 23.3%, while the other 2 types had no adverse reaction. Conclusions: Etanercept has a good therapeutic effect for JIA cases that mainly have articular lesions such as the oligoarticular type and polyarticular type. The adverse reactions of short term (within 6 months) are rare, the long-term security and stability of joint recovery are subject to a large sample, multi-center long - term follow-up observational study. Etanercept can make So-JIA patients clinical remission, but infection and other adverse events should be strictly guarded against. We can consider Etanercept for the SO-JIA patients that the conventional treatment are of no effect or SO-JIA patients merge with MAS.But some of patients applied with Etanercept may get worse, there are no reliable predictor for this by now. The Long-term efficacy and adverse reactions require further observation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5459